Pengembangan Buku Edukasi Bina Diri Toilet Training pada Siswa Tunagrahita Sedang - Khairiyah, Karunia Yulinda; Edi Kurniawan; Handoko, Supri (Universitas Lancang Kuning, 2024)
Moderately retarded children have a low ability to take care of themselves, namely toilet training, especially brushing their teeth properly. This is due to the cognitive barriers they have. In addition, the lack of learning media used is also one of the contributing factors. This study aims to overcome the low ability of self-brushing teeth in moderate mental retardation children in SLB YPBB Karimun by developing an educational book product for self-brushing teeth. The research subjects were TKLB moderate mental retardation students who were in SLB YPBB Karimun. The selection of research subjects is based on the results of the ability of self-help brushing teeth, which is still low but can still be directed. The type of research used is Research and Development / R&D (Research and Development). This research uses a Mental retardation research design supported by a quantitative approach. Based on the validity test of several experts, the results were obtained; media experts with an average value of 3.0 with the criteria